Le rovine dell’Avana tra realtà e finzione - Viola Gastaldi (Restauro Archeologico, 2015)
The morphology of the city of Havana is characterized by a unique architectural configuration that exerts a strong influence on the lives of its inhabitants. This reality can be seen through the eyes of various Cuban writers that emphasize many paradoxical aspects of the habanero’s life, who finds himself living daily amongst beauty and decay; aspects that, amazingly, manage to coexist in many of the ruined buildings of Habana Vieja and Centro Habana, the two districts of the historical city centre. The goal of this work is to extrapolate the specific element of the ‘ruin’ from a selection of contemporary Cuban literature and to present the connection to the people, nature and symbolism that the ruin takes on at a societal level, both as an entity in itself, as well as in connection with the city of Havana as a whole.